Pelaksanaan Pemeliharaan Sarana Prasarana sebagai Upaya Mewujudkan Kualitas Layanan Pendidikan - Iqbal, Muhammad; Febriyanti; Zulkipli (El-Idare, 2024)
This study aims to analyze the implementation and impact of the maintenance of facilities and infrastructure at SMP Nurul Qomar Palembang. The research is conducted using a descriptive qualitative approach, involving observation, interviews, and documentation to explore in-depth information on the quality and effectiveness of school facility maintenance. Research informants include the school principal, vice principal, head of administration, and teachers. The results show that although SMP Nurul Qomar has implemented maintenance procedures including routine maintenance and emergency repairs, there are significant challenges related to budget constraints and human resources. The quality of maintenance service is considered adequate, but there are issues in coordination and communication between technical staff and facility users. Technical skills also need improvement to effectively handle facility damage. The study reveals that good maintenance of facilities and infrastructure has a positive impact on the learning environment, student motivation, and teacher performance. Well-maintained facilities support the teaching and learning process, enhance student discipline and achievement, and facilitate teachers' work. With a structured maintenance system and regular evaluations, SMP Nurul Qomar can create an optimal learning environment. The study recommends improvements in communication, technical staff training, and budget management to enhance facility maintenance quality and support educational goals at the school.